IPO performance at announcement and in the aftermarket. Issue 4 (12th September 2016) - Abraham, Rebecca; Harris, Judith; Auerbach, Joel
Abstract : Purpose: The purpose of this paper is to investigate IPO performance. At announcement, the impact of purchases by informed traders on stock returns and uninformed traders on volatility were assessed. In the post-IPO period, returns were expected to be driven by firms with high returns on equity and the implementation of growth strategies. Return on equity was evaluated further in terms of whether it had a direct effect or was instrumented by volatility, cash flow, profit margin or revenue growth. Design/methodology/approach: All IPOs announced in 2009-2014 were used. Measures were created to demarcate growth firms from risk-averse firms and firms with highly volatile cash flows from their counterparts with cash flows of lesser volatility. Event studies were used to measure abnormal return and abnormal volume, while multiple regressions tested the influence of predictors on abnormal returns, volatility and holding period return. Instruments of return on equity were also assessed. Findings: The offer volume of informed traders significantly explained announcement-day returns, while the offer volume of uninformed traders explained the increase in volatility of IPO stock. The ability to capitalize on growth opportunities and increase shareholder wealth through higher return on equity significantly predicted holding period returns. Return on equity, was explained by volatility, cash flow to assets and profit margin. Originality/value: The data are highly current with 2014 IPOs being used. The paper clearly distinguishes between fleeting announcement-day returns driven by informed traders and long-term holding period returns in a departure from the prevailing practice of measuring long-term post-IPO performance with abnormal returns. Finally, the paper creates subjective measures of volatility and growth strategies.